Japan : Economic and Policy Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This paper provides a brief overview of the causes of the poor economic performance of Japan in the 1990s, and a more detailed analysis of developments in the real sector during 1999. The paper highlights that the collapse of the asset price bubble in 1990-91 provided the trigger for the downturn in 1992, and compounded the economic problems thereafter through its effects on the banking system. This paper also analyzes the fiscal policy developments and the monetary developments in Japan.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet